ON THE OCCURRENCE OF FISH LARVAE IN THE MANORA CHANNEL, KARACHI - Khan, J Ali; Waqar, Talat (Indian Journal of Fisheries, 2011)
A study based on surface samples collected from three fixed stations over the years 1968-70 shows that the ichthyoplankton is very poor in the Manora channel obviously because, with considerable waste materials introduced from the iishing harbour, the oil and sewage from large number of ships and boats and the discharge received from the Lyari river, to which the sewerage system of Karachi city is linked, the channel is now unfit to sustain a larval fish population of any magnitude. The fish larvae, mainly belonging to 24 identified families, are being brought into the channel with the tidal flow, ideally when the tidal height is 2-2.5 m. But these larvae, especially the smaller ones, return back with the tide, and whatever larvae remain are either confined to the lower harbour or suffering mortality. The yearwise and seasonwise distribution of the larvae of the various families are given along with graphs